DIGITAL TRANSFORMATION OF INSURANCE SERVICES IN UZBEKISTAN: PROBLEMS AND DEVELOPMENT TRENDS (Eureka Journal of Business, Economics & Innovation Studies, 2026)
The digital transformation of financial services has significantly influenced the modernization of insurance markets worldwide. In Uzbekistan, the insurance sector is undergoing structural and technological changes aimed at improving service accessibility, operational efficiency, and financial stability. This study analyzes the current state of digital transformation in insurance services in Uzbekistan, identifies existing challenges, and examines development trends within the framework of digital innovation. The research is based on institutional analysis, statistical data review, and comparative methods. The findings reveal that although significant progress has been achieved in electronic policy issuance, online platforms, and regulatory reforms, several barriers remain, including low digital literacy, limited InsurTech integration, cybersecurity risks, and insufficient data analytics infrastructure. The study concludes that strengthening digital ecosystems, adopting advanced data-driven risk assessment models, and enhancing regulatory support are essential for sustainable digital growth in Uzbekistan’s insurance sector.
Keywords: Digital transformation, insurance services, InsurTech, data analytics, financial innovation, Uzbekistan.